2013
DOI: 10.1074/jbc.m113.466540
|View full text |Cite
|
Sign up to set email alerts
|

IκB Kinase β (IKKβ) Inhibits p63 Isoform γ (TAp63γ) Transcriptional Activity

Abstract: Background:The functional regulation of p63 Isoform ␥ (TAp63␥) by IB Kinase ␤ (IKK␤) remains unknown, although they were previously shown to bind to each other. Results: IKK␤, but not its kinase dead mutant, suppressed the transcriptional activity of TAp63␥ by disrupting its interaction with p300. Conclusion: IKK␤ negatively regulates the transcriptional activity of TAp63␥. Significance: IKK␤ may favor cell proliferation by inhibiting TAp63␥ activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
(54 reference statements)
2
17
0
Order By: Relevance
“…It was previously reported that transcriptional activity of TAp63γ can be down‐regulated via phosphorylation at Ser12 by IκB kinase‐β (IKKβ) [38]. Being consistent with this, we found that S12A mutation, which mimics the dephosphorylation status, increases transcriptional activity of TAp63γ.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was previously reported that transcriptional activity of TAp63γ can be down‐regulated via phosphorylation at Ser12 by IκB kinase‐β (IKKβ) [38]. Being consistent with this, we found that S12A mutation, which mimics the dephosphorylation status, increases transcriptional activity of TAp63γ.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that IκB kinase β (IKKβ) phosphorylates Ser12 in TAD of TAp63γ and decreases its transactivity [38]. In this study, we found that JNK1 directly binds to TAD fragment of TAp63γ and inhibits its transcriptional activity.…”
Section: Introductionmentioning
confidence: 63%
“…The binding of TAp63γ to the putative responsive elements within the CCDC3 enhancer was also confirmed by chromatin immunoprecipitation (ChIP) analysis when HaCat cells, an immortal keratinocyte cell line 15 , with overexpression of flag-TAp63γ were treated with metformin to activate TAp63 transcriptional activity 5 (Fig. 1f ).…”
Section: Resultsmentioning
confidence: 69%
“…Next, we determined if CCDC3 expression is responsive to reagents or signals that affect TAp63 activity. Since our previous study showed that TNFα inhibits TAp63 transcriptional activity 15 , we first tested if TNFα could also inhibit CCDC3 expression. Indeed, this was the case, as treatment of MCF7 cells with TNFα led to the suppression of CCDC3 expression at both the mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation